Effect of Alcoholic Extract of Scrophularia Striata on Improving Spatial Memory in the Model of Crystal Meth Addiction in Male Rats - Somayyeh Hatami; Homeira Hatami; Farzam Sheikhzade; Gholamrez Dehgan (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2020)
Introduction: Crystal meth by induction of free radical formation in brains cells and lipid peroxidation cause to the apoptosis. The aim of present study is to investigate the effect of extract of Scrophularia striataon spatial memory, lipid peroxidation and alteration of antioxidant enzymes levels. Methods: In this experimental study, 42 male Wistar rats were divided into 6 groups, including: sham (saline), crystal meth (10, 15 mg/kg), Scrophularia Striate extract (200 mg/kg) and pretreatment of Scrophularia (200 mg/kg) + crystal (10, 15 mg/kg). Induction of addiction was performed by intra peritoneal injection of crystal meth during 5 consecutive days. Morris Water Maze was used for analyzing spatial memory. The levels of oxidative stress enzymes were assayed. Instate 3 was used for data analysis and the statistical test was One- Way ANOVA following by Tukey posthoc test. Results: Crystal meth reduced spatial memory (control: 18/59±6/34, crystal meth (10 mg/kg) 30/34±4/83, crystal meth (15 mg/kg): 59/98±0/77) (p<0.001). Pretreatment of Scrophularia improved the spatial memory (control: 18/59±6/34, Pretreatment of Scrophularia + crystal meth (10 mg/kg): 30/12±2/71, Pretreatment of Scrophularia + crystal meth (15 mg/kg): 50/43±0/51) (P<0.05). MDA, SOD and KAT levels increased in crystal meth group (P<0.05), but pretreatment of Scrophularia reduced the elevated level of MDA, SOD and KAT (P<0.05). Conclusion: It seems pretreatment of Scrophularia improve spatial memory which has been reduced by crystal meth.